2009
DOI: 10.1111/j.1467-9280.2009.02281.x
|View full text |Cite
|
Sign up to set email alerts
|

Reward Priority of Visual Target Singletons Modulates Event-Related Potential Signatures of Attentional Selection

Abstract: We examined visual search for color singleton targets, whose shape was discriminated. Critically, we varied the reward priority of singleton colors (correct fast performance for red singletons was worth more "bonus points" than for green singletons, or vice-versa), while testing whether ERP signatures of visual selection can be affected by distinct reward priorities for different target types, even when every target has to be selected for report. The N2pc component was earlier and larger for high-versus low-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
180
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(206 citation statements)
references
References 34 publications
25
180
1
Order By: Relevance
“…Attentional inhibition was found for task-irrelevant distractors (Raymond, Fenske, & Tavassoli, 2003), and it has been proposed that distractor suppression may be sensitive to reward contingencies (Della Libera & Chelazzi 2009). These results suggest that motivation can affect early visual processing enhancing selective attentional processing, showing that the attentional selection of target stimuli can be modulated by their reward value (Kiss et al, 2009).…”
Section: Reward-related Recognition Memorymentioning
confidence: 93%
See 1 more Smart Citation
“…Attentional inhibition was found for task-irrelevant distractors (Raymond, Fenske, & Tavassoli, 2003), and it has been proposed that distractor suppression may be sensitive to reward contingencies (Della Libera & Chelazzi 2009). These results suggest that motivation can affect early visual processing enhancing selective attentional processing, showing that the attentional selection of target stimuli can be modulated by their reward value (Kiss et al, 2009).…”
Section: Reward-related Recognition Memorymentioning
confidence: 93%
“…It has been proposed that an enhanced neural interaction between reward-related regions and areas involved in perceptual and cognitive processing improves behavioral performance to maximize the reward outcome (Pessoa, 2009). For example, some studies have provided evidence that motivation and attention jointly influence visual orienting by modulating early sensory processes (Engelmann & Pessoa, 2007;Kiss, Driver, & Eimer, 2009;Rutherford, O'Brien & Raymond 2010). In this regard, Rutherford and coworkers suggested that prior experience of reward might influence visual selection.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that our visual search task is broadly insensitive not just to spatial reward magnitude learning but to many forms of magnitude learning. As mentioned in the introduction, several researchers have reported robust prioritization of features that are associated with greater monetary reward (e.g., Anderson, et al, 2011;Kiss et al, 2009;Navalpakkam et al, 2010). In Experiment 2, we test whether the visual search task used in Experiment 1 produces learning of feature magnitude.…”
Section: Methodsmentioning
confidence: 99%
“…Just one study has reported that individuals learn to bias spatial attention to locations containing more valuable targets . Note that, overall, the number of studies of attention and reward have surged in recent years, most of which have shown robust prioritization of rewarded nonspatial features (e.g., Anderson, Laurent, & Yantis, 2011;Della Libera & Chelazzi, 2006;Hickey, Chelazzi, & Theeuwes, 2010;Kiss, Driver, & Eimer, 2009;Navalpakkam, Koch, Rangel, & Perona, 2010). Given the traditionally strong focus of attention research on spatial attention (Bisley & Goldberg, 2010;Fecteau & Munoz, 2006), one might expect more published studies demonstrating learning of spatial reward magnitude.…”
mentioning
confidence: 99%
“…Kiss, Driver, and Eimer (2009) showed that the selection of targets associated with high reward is facilitated relative to low reward targets during visual search. This occurs when both high and low reward targets are physically salient, and therefore assumed to be equally prioritised via bottom-up processes (e.g., Theeuwes, 1991).…”
Section: Learning To Attend: Effects Of Predictiveness On Perception mentioning
confidence: 99%